The Influence of the Teachings – Rituals of the Tarekat on the Management of Mental Education of the Young Generation: (Study on the Sufism-Tarekat of Syaikh Abi Hasan As-Syadzily at the Pesantren PETA Tulungagung) - Moch Solich (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
The world of tarekat which initially often got a pejorative meaning, anti-progress, identical with decline and old community groups and accused of being an institution that distances itself from the reality of worldly life, Tarekat with all its teachings-rituals aims to achieve a clean heart, This goal is what raises a big question whether there is an Influence of Tarekat Teachings-Rituals on the Management of Mental Education of the Young Generation? This study uses a qualitative descriptive method with a phenological approach. Type of case study. The source of research data is carried out through primary and secondary data sources. Primary data sources include the words and actions of the tarekat leader (mursyid), group leader and students. While secondary data sources consist of written materials/literature and observations. it can be concluded that: The ritual teachings of the Syadziliyyah tarekat at Pesantren PETA include: istighfar, Sholawat Nabi Muhammad. Saw, dzikir naive isbat and ismu dzat, walislah or tawasul, robithoh, wirid, hizib, adab mahasiswa and suluk. Meanwhile, the rituals of the Tarekat Syadziliyah include ba’iat or talqin, khususiyah and manaqib. The implications of the teachings of the tarekat ritual on the Management of Mental Education of the Young Generation are the perfection of commendable morals. Which is done through several stages, including istighfar which is the initial step for a student or salik to empty themselves (takhalli), cleanse the heart (Tashfiya al-qolb) and purify the soul (tazkiya al-nafs). The next step is to fill the heart and soul with good deeds (tahalli) including by reciting prayers to the Prophet Muhammad Saw. As a means to open the doors to Allah, such as dzikir naive isbat and ismu dzat, namely saying Lailahaillah and lafadz Allah, which was previously preceded by wasilah to the mursyid to the prophet saw.